Pengembangan Media Pembelajaran Buku Digital Interaktif Berbasis Pendekatan Matematika Realistik untuk Meningkatkan Kemampuan Spasial Siswa - Cici Puspaningrum; Edi Syahputra; Edy Surya (Study Program of Mathematics Education of Unimed Postgraduate Program, 2021)
This study aims to: 1) develop an interactive digital book learning media based on a realistic mathematics learning approach on the valid, practical, and effective flat-sided geometry material (cubes and blocks) so as to improve students' mathematical spatial abilities; 2) improve students' mathematical spatial abilities by using interactive digital books based on a realistic mathematics learning approach on the flat side (cube and block) material. This research is a development research using the ADDIE model. The validity of the interactive digital book learning media assessed by the validators in terms of three aspects, namely the quality of content and objectives, learning/instructional strategies, and media design obtained a total average of 3.73 (